Prevalence and Determinants of Osteoporosis Among Adults - Atheer Shehab Ahmed; Ahmed Khalid Abdullah; Sara Fawzi Sahm (Academia Open, 2025)
General background: Osteoporosis is a major global health concern, particularly among older adults and women, due to its association with fragility fractures, disability, and mortality. Specific background: In Iraq, limited research has examined the prevalence and determinants of osteoporosis, despite rising cases linked to aging and lifestyle factors. Knowledge gap: Few population-based studies have systematically explored the interaction of biological, reproductive, and lifestyle factors in shaping osteoporosis risk in Diyala province. Aim: This study investigated the prevalence of osteoporosis and identified significant risk factors among adults in Diyala. Results: A cross-sectional analysis of 190 participants (130 females, 60 males; aged 21–80) revealed a significant association between osteoporosis and factors such as menopause, breastfeeding practices, pregnancy number, and oophorectomy (p < 0.001). Age and gender were also significantly associated with prevalence, with women disproportionately affected. Novelty: Unlike prior studies that mainly assessed bone density, this research integrates demographic, reproductive, and lifestyle variables to clarify their relative contributions in a Middle Eastern context. Implications: Findings highlight the urgent need for targeted prevention programs, including lifestyle modification and public health education, to mitigate osteoporosis burden in Iraq and similar settings. Highlights: Osteoporosis prevalence is significantly higher in women, especially postmenopausal. Key risk factors include menopause, pregnancy history, breastfeeding, and oophorectomy. Findings emphasize the need for prevention through education and lifestyle modification. Keywords: Osteoporosis, Osteopenia, Premenopausal.